(untitled) (The Journal of Plant Protection Sciences, 2022)
Mustard aphid, Lipaphis erysimi (Kalt.), is the most serious insect-pest of rapeseed- mustard and responsible for causing the yield losses ranging from 35.4 to 96 per cent depending upon weather condition. The experiment was carried out to assess it’s incidence and their management during the winter seasons of 2009-10, 2010-11 and 2011- 12 at the Pulses and Oilseeds Research Station, Berhampore, West Bengal (India). The natural appearances of the aphid on the yellow sarson variety, Binoy (B-9) was observed from 52nd standard week, with the peak population on 6th standard week and the aphid disappeared after 10th standard week. Among the different chemical insecticides evaluated for their bio-efficacy against L. erysimi, Dimethoate 30EC and Oxydemeton-methyl 25EC were proved to be more effective. The plots treated with Dimethoate and Oxydemeton-methyl recorded minimum aphid infesta tion in most of the observations, there by produced more yield ranging from 1151.6 to 1310.3 kg seed/ha. Incre mental cost benefit ratio indicated that most favourable return was obtained under Dimethoate 30EC (1:20.8 & 1:13.3) followed by Oxydemeton-methyl 25EC (1:16.8 & 1:9.1), while poor incremental cost-benefit ratio was observed in Fipronil 5SC (1:5.8 & 1:2.1) and Acephate 75 SP (1:7.1& 1:4.3) during the year 2010-11 and 2011-12, respectively.